1999
DOI: 10.1002/(sici)1098-2795(199902)52:2<126::aid-mrd2>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and molecular cloning of cathepsin D from lizard ovary: Changes in enzyme activity and mRNA expression throughout ovarian cycle

Abstract: During vitellogenesis, the oocytes of oviparous species accumulate in the cytoplasm a large amount of proteic nutrients synthetized in the liver. Once incorporated into the oocytes, these nutrients, especially represented by vitellogenin (VTG) and very low-density lipoprotein (VLDL), are cleaved into a characteristic set of polypeptides forming yolk platelets. We have studied the molecular mechanisms involved in yolk formation in a reptilian species Podarcis sicula, a lizard characterized by a seasonal reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The results reported here show the presence in lizard of an aspartic proteinase form distinct from the cathepsin D previously described in the same organism (De Stasio et al, 1999); sequence analysis established for the new lacertilian sequence features typical of nothepsin. However, at variance with fish, lizard nothepsin is constitutively expressed in both males and females.…”
Section: Introductionsupporting
confidence: 59%
“…The results reported here show the presence in lizard of an aspartic proteinase form distinct from the cathepsin D previously described in the same organism (De Stasio et al, 1999); sequence analysis established for the new lacertilian sequence features typical of nothepsin. However, at variance with fish, lizard nothepsin is constitutively expressed in both males and females.…”
Section: Introductionsupporting
confidence: 59%
“…Both reproduction and self-maintenance require protein, and the immunosuppressive effects of pregnancy are well documented Martin, Weil, & Nelson, 2008), although most studies simply compare pregnant females with non-pregnant ones rather than assessing how allocation of energy to developing offspring change throughout pregnancy. Little is known about the timing of protein allocation to egg yolk in reptiles, and our assumption of a constant allocation rate is almost certainly incorrect (De Stasio, Borrelli, Kille, Parisi, & Filosa, 1999;Lourdais, Bonnet, Shine, & Taylor, 2003;Van Dyke & Beaupre, 2011). Vitellogenesis is the most resource-demanding stage of reproduction for many organisms, including reptiles (Thompson et al, 2001;Van Dyke & Beaupre, 2011), and there is some evidence that early reproduction is more energetically costly than later stages in small, heterothermic mammals (Christe, Arlettaz, & Vogel, 2000;Racey & Speakman, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have identified cathepsin proteases as key mediators of yolk processing during vitellogenic oocyte development in a wide variety of species (Fagotto, 1990;Nakamura et al, 1996;De Stasio et al, 1999;Gerhartz et al, 1999;Carnevali et al, 1999b). What remains enigmatic are the mechanisms by which multiple cathepsin proteases are differentially controlled during key developmental events involving proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence to suggest that the proteolytic processing of both vitellogenin and yolk platelets is mediated by cathepsins, a diverse family of serine, aspartate, and cysteine proteases. Cathepsins have been implicated in yolk processing in fishes (Kestemont et al, 1999;Carnevali et al, 1999a,b;Kwon et al, 2001;Hiramatsu et al, 2002;Wood and Van Der Kraak, 2003), amphibians (Yoshizaki and Yonezawa, 1996), reptiles (De Stasio et al, 1999), birds (Gerhartz et al, 1999), and insects (Yamamoto et al, 1994;Ribolla et al, 2001), suggesting an evolutionarily conserved role for these enzymes in vitellogenin and yolk processing.…”
Section: Introductionmentioning
confidence: 99%